Pancreatic panniculitis in a patient with pancreatic-type acinar cell carcinoma of the liver – case report and review of literature. Issue 1 (December 2016) - Zundler, Sebastian; Erber, Ramona; Agaimy, Abbas; Hartmann, Arndt; Kiesewetter, Franklin; Strobel, Deike; Neurath, Markus; Wildner, Dane
Abstract Background Pancreatic panniculitis is a rare condition, which has only been described in relation with pancreatic diseases up to now. It is characterized by necrotizing subcutaneous inflammation and is thought to be triggered by adipocyte necrosis due to systemic release of pancreatic enzymes with consecutive infiltration of neutrophils. We present the first case of a patient with pancreatic panniculitis caused by pancreatic-type primary acinar cell carcinoma (ACC) of the liver and without underlying pancreatic disease. Case presentation A 73-year old Caucasian female patient was referred to our department with painful cutaneous nodules persisting for eight weeks and with marked lipasemia ( 15000 U/l; normal range <60 U/l). Four weeks prior, several liver lesions had been detected. Empiric treatment with steroids did not show any effect. A biopsy of the skin nodules revealed "pancreatic" panniculitis, while abdominal imaging with ultrasound, computed tomography and magnetic resonance imaging detected no abnormal pancreatic findings. Ultrasound-guided biopsy of the liver lesions showed infiltrates of an ACC. The patient died soon thereafter. Autopsy failed to reveal any other primary for the ACC, so that a pancreatic-type ACC of the liver was diagnosed by exclusion. One hundred thirty cases of pancreatic panniculitis published within the last 20 years are reviewed. ACC of the pancreas is the most common underlying neoplastic condition. Patients with associated neoplasm are significantly older, take longer to be diagnosed and have higher lipase levels than patients with underlying pancreatitis. Extrapancreatic pancreatic-type ACC is very rare, but shows the same biological features as ACC of the pancreas. It is believed to develop from metaplastic or ectopic pancreatic tissue. Up to now, no pancreatic panniculitis in extrapancreatic ACC has been described. Conclusion Pancreatic panniculitis should always be included in the differential diagnosis of lipolytic panniculitic lesions. It can be regarded as a facultative paraneoplastic phenomenon. When suspected, a thorough work-up for identification of the underlying disease is mandatory and extrapancreatic lesions (e.g. liver) should also be considered. While administration of octreotide or steroids can sometimes alleviate symptoms, immediate treatment of the associated condition is the only effective management option.